PENINGKATKAN PEMBELAJARAN QUR’AN HADIS MELALUI PENDEKATAN METODE DEMONTRASI PADA SISWA KELAS III MIN 2 PANDEGLANG - Yajid; Nurul, Lilis; Aida Rosyidah, Neng (Ta'dibiya, 2022)
In learning Qur'an Hadis, students actually have potential that must be assisted in exploring and developing their potential by the teacher. So far, students tend to be only listeners, taking notes and doing assignments given by the teacher. So that learning is always monotonous, boring and less able to explore students' creativity. In fact, the teacher only uses the lecture method, question and answer and assignment. The reason is that this method is considered effective for conveying information and understanding about learning materials. This makes learning less interesting and boring, because students are passive, and only the teacher is active. The problems studied in this study are: the demonstration method can improve students' understanding in the Qur'an Hadis lesson on the subject of Memorizing Short Letters Fluently and Correctly in Class III students of MIN 2 Pandeglang in the 2018/2019 academic year and how the impact of learning activities teaching by using the demonstration method in the subjects of the Qur'an Hadith, the subject of Memorization of Short Letters Fluently and Correctly in Grade 3 students of MIN 2 Pandeglang in the 2018/2019 school year. The research method used is an elaborative and participatory method as a treatment of CAR research. It is carried out in 2 Siklus, each cycle consists of: planning, action, observation, and reflection stages. The data obtained in this study include: student activity taken from observation, student achievement taken from test questions at the end of each siklus, teacher and student activities during the learning process taken from observation sheets, results of interviews with students and teachers and documentation. The results of research with action and theoretical studies in this study, learning by using this demonstration can improve students' understanding in learning Qur'an Hadis and memorizing short letters fluently and correctly in grade 3 students of MIN 2 Pandeglang as well as increasing the process results. learning because students are active and feel happy to learn. This is in accordance with the theory that the application of the Demonstration Method in this learning has a positive impact in improving the process and student learning outcomes of learning the Qur'an Hadis.